A General Framework for the Solvatochromism of Pyridinium Phenolate Betaine Dyes - Caroli-Rezende, M; Aracena-Astudillo, A; Aracena-Astudillo, A (2013)
A general framework for the solvatochromic behavior of pyridinium phenolate betaine dyes is presented, based on the variations with the medium of the electrophilic Fukui functions of their electron-pair donor and acceptor moieties. The model explains the anomalous solvatochromic behavior of large betaines, which change their behavior from negative to inverted, when electron-pair donor and acceptor groups are separated by a conjugated chain of variable size. © 2012 Elsevier B.V. All rights reserved.